The Making of a Feminised Economy in the Gambia: Musu Kebba Drammeh and Batik Livelihood, 1940–2013 - Oladejo, Mutiat Titilope (Journal of Gender and Power, 2024)
This work examines the growth of Batik textile art in the works of Musu Kebba Drammeh in The Gambia. While African societies were swayed with the colonial economy, this paper unravels how textile art was a resilient economy, yet little scholarly attention is paid to it. Furthermore, it elucidates how sustainable livelihood reflects in the heritage and tradition of Kebba’s work in The Gambia. Livelihood process in her work creates a perspective to understand women’s influence on indigenous entrepreneurship. The fundamental objective is to analyse Kebba’s influence in the growth of Batik textile art in the Gambia. The historical method is adopted to explain the dynamics of times in the growth of Kebba’s work at Latrikunda. Most studies focus on the description of the art, with little reference to the actors involved and how the social, political and economic system influence their work.